THE CIVIL RESPONSIBILITY OF THE WHATSAPP GROUP ADMINISTRATOR: IN CASE OF OMISSION - da Conceição Gomes, Creuza; Moreira da Silva, Tenório (Revista Gênero e Interdisciplinaridade, 2023)
It is known that WhatsApp is the main communication application used today, however, a large number of people who use this technological tool still do not have a proper digital education, which generate very serious consequences, since such people post untruths and / or uncertain facts that end up being disseminated quickly across the internet. This article deals with the civil liability of the WhatsApp group administrator in case of omissions. It is necessary to emphasize the importance and speed of the positive feedback of the information contained in the social networks. However, some people, with the intention of denigrating the image of others, (re) produce texts with uncertainties, whose content are offenses, insults, which violate ethics and good customs, which generate several damages, mainly psychological ones for people who are involved in this practice. It is necessary to understand that WhatsApp groups are extremely important in the communicative process, but it is necessary to use them with netiquette, ethics in the use of the internet, given that there are laws that protect the flow of information on the internet. In this sense, there are also several judicial actions judged, in which sanctions were determined for those who disrespect others in the digital sphere. In the meantime, an analysis of the theory of civil liability provided for in Law No. 10,406 / 2002 will be made; emphasizing articles 186 and 927 of that law, in addition to explaining whether such law is sufficient to suppress offenses carried out in WhatsApp groups.